Valor predictivo del índice neutrófilo/linfocito y plaquetas/linfocitos de las características ecográficas presentadas por los pacientes pediátricos con diagnóstico de dengue hospitalizados en el servicio de pediatría del Hospital Regional Loreto, 2014-2019 - Vásquez Rodríguez, Génesis del Rosario (2023)
Unfortunately, the course of dengue infection is difficult to predict, even with the clinical classification described in management guidelines. In addition, the lack of specificity of the warning signs has caused an increase in hospital admissions. Therefore, it is critical to develop more accurate diagnostic tools or models in order to alleviate the burden of disease and improve management and treatment outcome. For this reason, the objective of this study was to determine the predictive value of the neutrophil/lymphocyte and platelet/lymphocyte ratio of the ultrasound characteristics presented by pediatric patients with a diagnosis of dengue hospitalized in the pediatric service of the Loreto Regional Hospital, 2014-2019. For this purpose, a quantitative study, of a predictive level, was designed. The sample consisted of 96 patients, selected using a simple random probabilistic sampling technique. The results showed that the platelet/lymphocyte ratio was significant in relation to the presence of ascites and edema of the gallbladder wall (p<0.05). Concluding that the platelet/lymphocyte ratio presents adequate validation parameters for the identification of ascites and edema of the gallbladder wall in the pediatric population diagnosed with dengue.